Preliminary design of next generation Mach 1.6 supersonic business jets to investigate landing & take-off (LTO) noise and emissions–SENECA - Mourouzidis, Christos; del Gatto, Dario; Adamidis, Stylianos; Villena Muñoz, Cristina; Lawson, Craig P.; Martinez Corzo, B.; Leyland, P.; Marsh, D.; Lim, L.; Owen, B. (Institute of Physics (IOP), 2023)
With the approach of next generation supersonic transport entry into service, new research activities were initiated to support updates on ICAO regulations and certification processes for supersonic transport vehicles. Within this context, the EU Horizon 2020 SENECA project has been launched to investigate the levels of noise and gaseous emissions in the vicinity of airports as well as the global climate impact of next generation supersonic civil aircraft. This paper introduces some of the preliminary outcomes of this investigation. It presents the preliminary design and performance analysis of a Mach 1.6 business jet, following an integrated aircraft-engine design approach. The preliminary design was performed accounting for the limitations posed by future environmental restrictions on respective subsonic vehicles. The market space and mission route definition exercise assumed only "over-sea" supersonic operations, while for "over-land", only subsonic operations where allowed. Parametric studies on engine integrated design demonstrated modest core temperatures while cruising and the significant impact of engine installation on performance. At this first design iteration, assuming current state of the art technology, the Mach 1.6 business jet showed good potential to satisfy the predicted mission requirements while respecting the environmental constraints in terms of Landing & Take-Off (LTO) noise and emissions.
12th EASN International Conference on "Innovation in Aviation & Space for Opening New Horizons", 18-21 October 2022, Barcelona, Spain